ACCUSATIO I INQUISITIO W PROCESIE KARNYM OKRESU CESARSTWA - Santalucia, Bernardo (Zeszyty Prawnicze, 2017)
ACCUSATIO AND INQUISITIO IN CRIMINAL PROCEEDINGS IN THE ROMAN EMPIRE PERIOD Summary Until recendy it has been considered in the Roman law studies that the proceedings before queastiones perpetuae materially differed from cognitio extra ordinem. It has been assumed that the former had the nature of the action of law proceedings, the latter of the inquisition proceedings. According to the majority of specialists, the proceedings before quaestiones were initiated by citizen’s action demanding — on behalf of the whole community - that a crime be prosecuted, while cognitio extra ordinem was initiated by an official ordering its police services to prosecute a crime. At present the above presented view has opponents, who underline the significance of the action also in the cognitio extra ordinem. In their opinion, this prevailing conviction is hardly possible to be accepted taking into account a correct analysis of the sources speaking of the action of lawproceedings being privileged against the inquisition proceedings. It is also claimed that the terminology and principles of the action of law proceedings maintained their dominant character irrespective of the developments of the inquisition proceedings, and the law developed harmoniously both in the publica iudicia and the cognitio extra ordinem area untilthe end of the Western Empire, which is confirmed by the leges from IV and V century. The author of this article does not share these opinions. He is sure that the older researchers were closer to the truth of the Roman criminal proceedings. The inquisitio of judges and officials, applied in the first centuries of the Empire, became common along with the development of the cognitive system to finally deprive the public action of its original significance - in the decline of the Roman Empire period it no longer conditioned initiating the proceedings and was only one of the means to inform about crimes, which were prosecuted by criminal repression ex officio.